2011
DOI: 10.1111/j.1939-1676.2011.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Aseptic Dogs with Hemorrhagic Gastroenteritis with Amoxicillin/Clavulanic Acid: A Prospective Blinded Study

Abstract: Background: Antibiotics generally are recommended to treat hemorrhagic gastroenteritis (HGE). Inappropriate use of antibiotics may promote risk of antimicrobial resistance and unnecessary adverse drug reactions. The necessity of antimicrobial therapy in dogs with HGE has not been demonstrated. Objective: The purpose of this prospective, placebo‐controlled, blinded study was to evaluate whether treatment with amoxicillin/clavulanic acid improves the clinical course and outcome of HGE in dogs that show no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 38 publications
6
95
2
2
Order By: Relevance
“…Although AHDS is typically described as acute-onset vomiting and haemorrhagic diarrhoea (Burrows 1977, Triolo and Lappin 2003, Unterer and others 2011), 20 per cent of the patients of the present study did not show vomiting at any time during disease course. If emesis occurs, this is not due to gastritis since a recent study showed that mucosal lesions associated with AHDS are restricted to the intestines (Unterer and others 2014).…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Although AHDS is typically described as acute-onset vomiting and haemorrhagic diarrhoea (Burrows 1977, Triolo and Lappin 2003, Unterer and others 2011), 20 per cent of the patients of the present study did not show vomiting at any time during disease course. If emesis occurs, this is not due to gastritis since a recent study showed that mucosal lesions associated with AHDS are restricted to the intestines (Unterer and others 2014).…”
Section: Discussioncontrasting
confidence: 60%
“…In humans, acute haemorrhagic enteritis caused by certain enterotoxigenic strains of Escherichia coli has a very similar clinical presentation (Triolo and Lappin 2003). In dogs, different aetiologies have been discussed, including intestinal type 1 hypersensitivity reaction to food components or bacterial endotoxin, and enterotoxigenic clostridial strains (Cave and others 2002, Triolo and Lappin 2003, Hall and German 2010, Unterer and others 2011, 2014). A rapid clinical improvement is typically seen with symptomatic therapy—aggressive fluid therapy being the mainstay of treatment (Triolo and Lappin 2003, Unterer and Hartmann 2009, Unterer and others 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Analgesics were administered dependent on clinical judgement of abdominal pain. The clinical assessment was performed by calculating the “canine HGE activity index.”2 This index includes the parameters attitude, appetite, vomiting, stool consistency, stool frequency, and dehydration. Each parameter was scored (0 = normal, 1 = mild, 2 = moderate, 3 = severe), and the sum of scores yielded a total cumulative score (maximum = 18).…”
Section: Methodsmentioning
confidence: 99%